Towards Agile Model-Driven Web Engineering - Rivero, José Matías (2011)
The increasing growth of the Web field has promoted the development of a plethora of Model-Driven Web Engineering (MDWE) approaches. These methodologies share a top-down approach: they start by modeling application content, then they define a navigational schema, and finally refine the latter to obtain presentation and rich behavior specifications. Such approach makes it difficult to acquire quick feedback from customers. Conversely, agile methods follow a non-structured, implementation-centered process building software prototypes to get immediate feedback. In this work we propose an agile approach to MDWE methodologies (called Mockup-Driven Development, or MockupDD) by inverting the development process: we start from user interface mockups that facilitate the generation of software prototypes and models, then we enrich them and apply heuristics in order to obtain software specifications at different abstraction levels. As a result, we get an agile prototype-based iterative process, with advantages of a MDWE one.